PERLINDUNGAN HUKUM BAGI DEBITUR (NASABAH) DALAM PELAKSANAAN PERJANJIAN KREDIT PERBANKAN DITINJAU DARI UNDANG-UNDANG PERLINDUNGAN KONSUMEN - Widyantini, Ni Luh Putu; Diantha, I Made Pasek (Kertha Wicara : Journal Ilmu Hukum; Vol.2, No.1 Edisi Februari 2013)
In scientific papers, entitled "Legal Protection for Debtor (Customer) OngoingBanking Credit Agreement Reviewed From Consumer Protection Law" was conceivedconcerns about weaknesses in the debtor position of the banking credit agreement and itsprovisions are standardized formulation unilaterally by the Bank. The method used toassess and analyze problems, among other types of normative legal research approachlegislation, legal materials collection techniques by conducting literature searches as wellas primary legal materials and secondary, as well as qualitative analysis techniques,descriptive and analytical systematic. Based on the analysis and the results obtained, dueto standard contract law requires the debtor to agree to and implement the provisions ofthe standard contract formulation and conditions are determined unilaterally by the Bank.In addition, the Consumer Protection Act has set the standard clause inclusion ofprovisions to protect the rights and interests of the debtor. The conclusion that the legalprotection for debtors in bank credit agreement lies in the obligation for the bank to heedthe standard clause-making procedures both in form and substance by the ConsumerProtection Act in terms of making a credit agreement / funding to protect the interests ofthe debtor (customer).
Keywords: Banking, Debtors, Standard Contract, Consumer Protection